Acute visual loss after ipilimumab treatment for metastatic melanoma. Issue 1 (December 2016) - Wilson, Melissa; Guld, Kelly; Galetta, Steven; Walsh, Ryan; Kharlip, Julia; Tamhankar, Madhura; McGettigan, Suzanne; Schuchter, Lynn; Fecher, Leslie
Abstract Background Ipilimumab, a humanized CLTA-4 antibody is a standard therapy in the treatment of advanced melanoma. While ipilimumab provides an overall survival benefit to patients, it can be associated with immune related adverse events (IrAEs). Case presentation Here we describe a patient treated with ipilimumab who experienced known IrAEs, including hypophysitis, as well as a profound vision loss due to optic neuritis. There are rare reports of optic neuritis occurring as an adverse event associated with ipilimumab treatment. Furthermore, the patient experienced multiple complications from high dose steroids used to manage his IrAEs. Conclusions This case highlights the need for recognition of atypical immune mediated processes associated with newer checkpoint inhibitor therapies including ipilimumab.